Peculiarities of course of operational and postoperative periods in appendectomy after various methods of the antibiotics introduction - I. D. Duzhyi; V. V. Shimko; G. I. Pyatikop; O. L. Sytnik; V. Ya. Pak (Клінічна хірургія)
Objective. To study the peculiarities of antibiotics accumulation in appendix vermiformis after various methods of their introduction.